2020
DOI: 10.1002/aocs.12338
|View full text |Cite
|
Sign up to set email alerts
|

Renewable Aliphatic Polyesters from Fatty Dienes by Acyclic Diene Metathesis Polycondensation

Abstract: Three renewable, linear, aliphatic polyesters were prepared by Acyclic diene metathesis (ADMET) polymerization of α,ω-dienes derived from fatty acids. Condensation of 9-decenoic acid with allyl 9-decenoate, ethylene glycol, and 9-decen-1-ol proceeded in high conversion (≥94%) and purity (>99%) to give α,ω-dienes suitable for subsequent polycondensation. Polymerization was achieved using 1.0 mol% Hoveyda-Grubbs second-generation metathesis catalyst in combination with 2.0 mol% 2,6-dichloro-1,4-benzoquinone as a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
22
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 14 publications
(25 citation statements)
references
References 68 publications
(95 reference statements)
3
22
0
Order By: Relevance
“…a The results thus clearly indicate the formation of polymers by ADMET polymerization. 22 34 , 43 59 The resultant polymers (PE1) possess a sole (rather sharp) melting temperature ( T m ) at 46.9 °C (run 3, M n = 15,900), whereas the T m value was affected by the molecular weight [Figure S39, Supporting Information , T m value = 46.9 °C ( M n = 15,900, run 3), 40.9 °C (12,400, run 6), 36.6 °C (8500, run 2), and 34.8 °C (7700, run 1)].…”
Section: Resultsmentioning
confidence: 99%
“…a The results thus clearly indicate the formation of polymers by ADMET polymerization. 22 34 , 43 59 The resultant polymers (PE1) possess a sole (rather sharp) melting temperature ( T m ) at 46.9 °C (run 3, M n = 15,900), whereas the T m value was affected by the molecular weight [Figure S39, Supporting Information , T m value = 46.9 °C ( M n = 15,900, run 3), 40.9 °C (12,400, run 6), 36.6 °C (8500, run 2), and 34.8 °C (7700, run 1)].…”
Section: Resultsmentioning
confidence: 99%
“…However, as shown in Figure a, the degree of the odd–even effect decreases with increasing number of methylene units as well as methylene units in the diol units ( X = 10 vs 20); the T m values thus are dependent on the total number of methylene groups and their distribution within the polymer chain . It was demonstrated that the T m values higher than 100 °C were achieved by increasing the percentage of long, , crystallizable methylene segments; the T m value should finally converge toward linear polyethylene by further increasing chain lengths of the aliphatic repeat units. ,, …”
Section: Synthesis Of Aliphatic Polyesters By Acyclic Diene Metathesi...mentioning
confidence: 99%
“…Synthesis of high-molecular-weight ( M n > 150,000) poly­(pentadecalactone) was achieved recently by using Al catalyst containing salen ligands. , More recently, numerous examples for catalyzed ROP of various lactones including large-membered rings have been reported; the progress will provide the possibility in the future. As described below, synthesis of the polymers by acyclic diene metathesis (ADMET) polymerization and subsequent hydrogenation can also be considered as the alternative route. ,,,,− ,,, …”
Section: Synthesis Of Aliphatic Polyesters By Acyclic Diene Metathesi...mentioning
confidence: 99%
See 1 more Smart Citation
“…As part of our continuing efforts to produce aliphatic polyesters from renewable starting materials (Moser et al, 2019, 2020), we were originally attempting to esterify 9‐decenoic acid with 4 in the presence of catalytic p TsOH in refluxing toluene to give the corresponding tris ‐unsaturated perillyl decenoate as a monomer for subsequent acyclic diene metathesis polymerization and thiol‐ene photochemical polycondensation. The esterification procedure had proven simple and effective for several previous condensations involving different alcohol/acid combinations (Moser, 2014; Moser et al, 2019, 2020), but in this case the expected ester was not observed. Instead, a mixture comprised of 4 , unreacted 9‐decenoic acid, and a curiously high amount of 1 (31%) was noted.…”
Section: Resultsmentioning
confidence: 99%